(untitled) (Global Journals of Research in Engineering, 2023)
The expediency of replacing the Clausius entropy with a more adequate concept of thermal impulse as a measure of the amount of disordered motion in the system is substantiated It is shown that the thermal impulse also exists in nonequilibrium systems where it can also both increase and decrease This makes it possible to solve the problem of thermodynamic inequalities to return the concept of force to thermodynamics to unify the methods for finding heterogeneous forces to propose simpler criteria for the equilibrium evolution and involution of each degree of freedom of the system separately to substantiate the unity of the laws of transformation of any form of energy to eliminate the blatant contradiction of thermodynamics with the nature of biological and cosmological evolution etc Other advantages of the thermal impulse are also revealed which facilitate the proof of its existence its applicability to thermally inhomogeneous media physical visibility measurability ease of eliminating a number of paralogisms of thermodynamics etc